The feasibility of psychomotor therapy in acute mental health services for adults with intellectual disability - Kay, Joshua J; Clegg, Jennifer A.; Emck, Claudia; Standen, Penny J. (Informa Healthcare, 2016)
Background. Psychomotor therapy enables people to reflect on the relationship between experiences and feelings by starting from awareness of bodily responses rather than from awareness of emotion. In this study we examine PsyMot (ID), an assessment that directs this psychological therapy.